2010
DOI: 10.1002/ctpp.200900051
|View full text |Cite
|
Sign up to set email alerts
|

Density Collapse Events Observed in the Large Helical Device

Abstract: A core density collapse (CDC) phenomenon is a rapid collapse events observed in super dense core (SDC) plasma with internal diffusion barrier (IDB) in the Large Helical Device (LHD). By CDC, the central beta is decreased by up to 50%. The collapse starts from the edge region of the plasma. CDCs appear with plasma parameters where the high-n ballooning modes are unstable at ρ ∼ 0.8. With less collisional conditions, m = 1 type oscillations are observed with similar beta profile. The origin of the m=1 oscillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…29 A candidate of the driving mechanism is the ballooning MHD instability, but it is still unclear. 33 In the high-central-beta scenario, the study of the MHD instability effect on the confinement is out of the scope of the present paper, and one of our future subjects.…”
Section: -8mentioning
confidence: 98%
“…29 A candidate of the driving mechanism is the ballooning MHD instability, but it is still unclear. 33 In the high-central-beta scenario, the study of the MHD instability effect on the confinement is out of the scope of the present paper, and one of our future subjects.…”
Section: -8mentioning
confidence: 98%
“…The importance of the interplay between the ITG turbulence and zonal flows in the large helical device (LHD) (Kaneko et al 2013), which is a heliotron device, was reported by the means of electrostatic gyrokinetic simulations with adiabatic electrons (Watanabe et al 2008), and it is reported that a neoclassical optimization of the magnetic configuration leads to the reduction of heat transport through the enhancement of zonal flows. The LHD plasma is normally free from the current driven instability, while the pressure driven instabilities such as ballooning modes can degrade the confinement of plasmas in high-beta discharges (Ohdachi et al 2010), and the threshold of KBM is normally lower than that of the ideal MHD ballooning mode (Tang et al 1980;Hirose 1994).…”
Section: Cyclone Base Case (Cbc) Tokamakmentioning
confidence: 99%
“…In the super-density core plasmas, which were obtained by repetitive pellet injection in the outward shifted LHD configurations, core density collapse phenomena are observed (Ohyabu et al 2006;Sakamoto et al 2007). From the MHD analysis for such plasmas, it is found that ideal ballooning modes with γ τ a ∼ 0.1 are unstable (Ohdachi et al 2010(Ohdachi et al , 2017. Since the linear growth rate is sufficiently larger than the precession drift frequency of the deeply trapped ions, i.e.…”
Section: Discussionmentioning
confidence: 99%